Pulmonary metastasis of a meningioma presenting as a solitary pulmonary nodule: 2 case reports. Issue 2 (3rd March 2016) - Leemans, J.; Van Calenbergh, F.; Sciot, R.; Debiec-Rychter, M.; Decaluwe, H.; Nackaerts, K.
Abstract : Distant metastases of meningioma are rare, especially in grade 1 meningiomas. In a recent literature review, only 115 cases were found. In almost all published cases, the meningioma was treated several years before the metastasis was diagnosed. The lungs are the most frequent site of metastasis. We describe two patients treated for meningioma (one case grade 1, the other grade 3) who were referred to the Respiratory Oncology Unit because of the incidental finding of a pulmonary nodule on routine chest radiography. Both had undergone several neurosurgical procedures but the last operation was more than 7 years before in both cases. Positron emission tomography scan was suggestive of a malignant lung tumour. The lesions were surgically removed. Pathology confirmed meningioma in both cases with the same WHO grade, immunohistochemical and genetic profiles as the original meningioma. Both patients recovered well from thoracic surgery. The patient with grade 3 meningioma died three years later from intracranial recurrence. When a patient previously treated for meningioma develops a nodular lung lesion, metastasis of the meningioma should be in the differential diagnosis list. Because of the occurrence of distant metastasis even in grade I meningiomas, we suggest that the grading system should take into account genetic changes in the meningioma. Chromosome 1p and 14q losses possibly explain the aggressive behaviour of the grade 1 meningioma.